Synthetic Lipopeptide Enhances Protective Immunity Against Helicobacter pylori Infection - Xue, Ruo-Yi; Guo, Mu-fei; Guo, Ling; Liu, Chang; Li, Sun; Luo, Jiao; Nie, Li; Ji, Lu; Ma, Cong-Jia; Chen, Da-Qun; Sun, Si; Jin, Zhe; et al. (Frontiers in Immunology, 2019)
More than half of the world's population is infected with Helicobacter pylori (H. pylori), which is the main cause of gastric diseases such as chronic gastritis and stomach cancer. H. pylori adhesin A (HpaA) is a surface-located lipoprotein, which is essential for bacterial colonization in the gastric mucosa. HpaA had been proposed to be a promising candidate antigen for H. pylori vaccines. However, the effect of non-lipidated recombinant HpaA (rHpaA) to stimulate immune response was not very ideal, and the protection against H. pylori infection was also limited. We hypothesized that low immunogenicity of rHpaA may attribute to lacking the immunostimulatory properties endowed by the lipid moiety. In this study, two novel lipopeptides, LP1 and LP2, which mimic the terminal structure of the native HpaA (nHpaA), were synthesized and TLR2 activation activity was confirmed in vitro. To investigate whether two novel lipopeptides could improve the protective effect of rHpaA against H. pylori infection, groups of mice were immunized either intramuscularly or intranasally with rHpaA together with LP1 or LP2. Compared with rHpaA alone, the bacterial colonization of the mice immunized with rHpaA plus LP2 via intranasal route was significantly decreased and the expression levels of serum IgG2a, IFN-γ and IL-17 cytokines in spleen lymphocyte culture supernatant increased obviously, suggesting that the enhanced protective effect of LP2 may be associated with enhanced specific Th1 and Th17 responses. In conclusion, LP2 has been shown to improve the protective effect of rHpaA against H. pylori infection, which may be closely related to its ability to activate TLR2 by mimicking the terminal structure of nHpaA.